The effectiveness of peer-assessment in increasing students’ ability in writing descriptive text - Faradila Nursamsi; Nur Sehang Thamrin; Moh. Abraham Akbar Eisenring; Sriati Usman (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study aims to prove whether Peer Assessment can improve students' ability in writing descriptive text. This study investigates peer assessment (PA) as a learning strategy, focusing on students' ability to apply writing knowledge to descriptive texts. To address this, the researchers used a quasi-experimental design. The population of this study was eleventh-grade students at Untad Palu Lab School. The researchers took class XI MIPA 1 (18 students in the experimental group) and XI MIPA 3 (18 students in the control group) as samples by using the purposive sampling technique. This study utilized a pre-test and post-test, with data analysis conducted using the Mann-Whitney test (SPSS 24). The Mann-Whitney test was employed to compare two independent groups with ordinal or interval data that were not normally distributed. The results showed that the test statistic was 0.000, which is less than 0.05, which indicates that the null hypothesis was rejected and the alternative hypothesis was accepted. The findings suggest a significant difference in learning outcomes between the experimental and control groups. It was concluded that PA had a significant influence on students' learning outcomes in writing descriptive text with correct English grammar. The results of this study provide valuable insights for students, teachers, and future researchers, highlighting the potential of PA to improve students’ language skill in English as a Foreign Language (EFL) settings.